Remedies for Contractual Non-Performance under French Law - A. V. Padiryakov; R. V. Barabash (Московский журнал международного права, 2016)
This survey presents overview of damages and other contractual remedies of French law and its comparison in some aspects with law of England. The present comparison of damages and other contractual remedies available to parties to a contract under French and English laws shows the differences of legal systems to which the said countries belong. The differences in the legal systems entail the differences in remedies and its implementation. There are remedies under the law of England which French law is rather reluctant to uphold and there are remedies not very well developed in England but widely spread in France (at first hand punitive damages and specific performance). The implementation of the same remedy could have different mechanics and even different ideology.